2011
DOI: 10.2337/db10-1332
|View full text |Cite
|
Sign up to set email alerts
|

GIP Does Not Potentiate the Antidiabetic Effects of GLP-1 in Hyperglycemic Patients With Type 2 Diabetes

Abstract: OBJECTIVEThe incretin glucagon-like peptide 1 (GLP-1) exerts insulinotropic activity in type 2 diabetic patients, whereas glucose-dependent insulinotropic polypeptide (GIP) no longer does. We studied whether GIP can alter the insulinotropic or glucagonostatic activity of GLP-1 in type 2 diabetic patients.RESEARCH DESIGN AND METHODSTwelve patients with type 2 diabetes (nine men and three women; 61 ± 10 years; BMI 30.0 ± 3.7 kg/m2; HbA1c 7.3 ± 1.5%) were studied. In randomized order, intravenous infusions of GLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
145
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(159 citation statements)
references
References 55 publications
9
145
3
2
Order By: Relevance
“…It was recently reported that GIP infusion antagonizes the glucagonostatic effects of GLP-1 in hyperglycemic patients with type 2 diabetes [8]. Although active GIP levels were increased by sitagliptin in the present subjects, glucagon levels were reduced, indicating that the glucagonostatic effect of increased GLP-1 was superior to the glucagonotropic effect of enhanced GIP activities.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…It was recently reported that GIP infusion antagonizes the glucagonostatic effects of GLP-1 in hyperglycemic patients with type 2 diabetes [8]. Although active GIP levels were increased by sitagliptin in the present subjects, glucagon levels were reduced, indicating that the glucagonostatic effect of increased GLP-1 was superior to the glucagonotropic effect of enhanced GIP activities.…”
Section: Discussioncontrasting
confidence: 43%
“…A glucagon suppressive effect is one of these possible mechanisms. However, since DPP-4 inhibitors augment plasma activities of both GLP-1 and GIP, the latter being capable of antagonizing the glucagonostatic effect of the former [8], it is not clear whether DPP-4 inhibitors cause glucagon suppression in hyperglycemic insulin-treated type 2 diabetes patients.…”
Section: Meal Tolerance Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, insulin levels were higher for L-glutamine vs. placebo only after 90 min, at which time the plasma glucose had already peaked and was decreasing. Given the expected lag (60-90 min) between elevating insulin levels and observing its effect on glucose lowering, a full effect on blood glucose would not be seen till 150 min to 180 min after the glucose challenge, as demonstrated by Nauck's group [48], which is outside the observation range in this study. Notably, there was an expected lag between peak GLP-1 secretion (at approximately 30 min) and peak insulin secretion (at approximately 90 min) in this study.…”
Section: Discussioncontrasting
confidence: 53%
“…However, during hyperglycemia GLP-1 is more insulinotropic than GIP. Importantly, in most cases, GLP-1 maintains its insulinotropic effect in diabetic patients, but not GIP [14][15][16][17].…”
Section: The Incretin Conceptmentioning
confidence: 99%